Nest predation and daily survival rates of three Hawaiian endemic species - Aaron J Works; Lindsey Nietmann; Taylor Shimabukuro; Kristen Harmon; Jaime A Botet Rodriguez; Melissa R Price (Journal of Field Ornithology)
Specific State Wildlife Sanctuaries have been identified as core wetlands for the recovery of endangered waterbirds in Hawaiʻi. Hawaiian waterbirds require direct management of habitat and invasive predators for their survival. Therefore, it is crucial to identify seasonal nesting patterns and specific nest predators to improve nesting success. Hāmākua Marsh and Kawainui Marsh, two State Wildlife Sanctuaries, were surveyed weekly for Hawaiian Coot ( Fulica alai ), Hawaiian Common Gallinule ( Gallinula galeata sandvicensis ), and Hawaiian Stilt ( Himantopus mexicanus knudseni ) nests from 2020 through 2023. Some nests were monitored with passive infrared cameras ( n = 240), and all nests were manually observed twice per week until the fate of the nest was determined. Nest phenology was recorded for all nests, and predation events were determined through camera photos or predator forensics. The seasonal nesting patterns for coots and gallinules showed weakly bimodal distributions, while stilt nesting was unimodal. A total of 395 nests were discovered (coot [ n = 115], gallinule [ n = 164], and stilt [ n = 116]), out of which 59 had unknown fates, 156 failed (46%), and 180 were successful (54%). The daily nest survival rates at Hāmākua were higher for coots (0.975), gallinules (0.973), and stilts (0.972) compared with Kawainui (0.962, 0.942, and 0.969, respectively). Nest failure events documented with cameras were predominantly due to predators at Kawainui (58%) and abandonment at Hāmākua (51%). Nest predation events accounted for 43% (coots), 38% (gallinules), and 55% (stilts) of the confirmed nest failures. The small Indian mongoose ( Urva auropunctata ) was identified as the primary predator responsible for 76% of predator-caused nest failures at both marshes combined. The findings suggest that conservation efforts for Hawaiian waterbirds in Hawaiʻi should prioritize predator control, particularly focusing on the invasive mongoose, to enhance nest success.